The role of Bill of materials and movements (BOMM) in the virtual enterprises environment - Pires, Luís (2012)
Organizing and managing dynamic networks of enterprises (or virtual enterprises (VE)) is a very complex task and many issues are still to be effectively covered. Apart from the models that can be used to create and manage VEs, product data play a central role in the VE life cycle. VE composition, interaction among VE members (Autonomous Production Systems in this work), as well as its relationship with the market, is severely dependent on the product technical specifications as well as on the product process planning information. In traditional managing systems for the single enterprise environment the Bill of Materials (BOM) plays that role and in this paper is proposed a Bill of Materials and Movements (BOMM) as its equivalent in VE environments. The BOMM includes product structure, high level process planning information and some degree of VE composition. BOMM is present during VE formation, operation, and reconfiguration, playing a central role in the material detailed planning and in the movement planning between VE members. In this article the BOMM role during the VE life cycle is described in detail.